2022
DOI: 10.3389/fimmu.2022.905930
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia Correlates With Glomerular Phospholipase A2 Receptor Deposit and Serum Anti-Phospholipase A2 Receptor Antibody and Predicts Proteinuria Outcome in Idiopathic Membranous Nephropathy

Abstract: BackgroundThe anti-phospholipase A2 receptor (PLA2R) antibody is a non-invasive diagnostic tool and prognosis predictor of idiopathic membranous nephropathy (IMN). Baseline hypercholesterolemia independently predicts proteinuria outcomes in IMN patients. Thus, we investigated whether hyperlipidemia is correlated with anti-PLA2R and pathological indicators.MethodsA total of 495 IMN patients identified by kidney biopsy in Wuhan Tongji Hospital, China, from January 2016 through December 2020 were enrolled in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…PLA2G12B is a member of the PLA2 family, and PLA2 antibodies have been shown to be key antibodies in MN [4, 19]. A prospective clinical study showed that immunosorbent alleviated early MN by removing PLA2 antibodies with good safety and tolerability [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PLA2G12B is a member of the PLA2 family, and PLA2 antibodies have been shown to be key antibodies in MN [4, 19]. A prospective clinical study showed that immunosorbent alleviated early MN by removing PLA2 antibodies with good safety and tolerability [17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lipid metabolism such as cholesterol metabolism and AA metabolism is closely related to the prognosis of MN [20]. Hypercholesterolemia was proven to be associated with glomerular PLA2 receptor deposition and independently predicted proteinuric outcome in patients with MN [4]. Dong et al [21] reviewed 256 patients with MN diagnosed by renal biopsy, and lipid profiling found that non-HDL levels correlated most strongly with proteinuria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, accumulating data have been pointing to the important role of biomarkers for evaluating immune status such as a proliferation-inducing ligand, serum complement 4, Interleukin-35 levels [ 14–16 ], and for reflecting tubular injury in PMN [ 19 ]. Besides, risk factors of metabolic syndrome such as body mass index (BMI), total cholesterol (TC), non-high-density lipoprotein cholesterol (non-HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglycerides (TG) are also demonstrated to be associated with renal outcomes in PMN [ 17 , 18 ]. However, the relationship between renal histological features and renal prognosis is controversial to some extent due to the lack of sufficient attention and data support [ 20 ].…”
Section: Introductionmentioning
confidence: 99%